Pengaruh Pendidikan Kesehatan dengan Media Cerpen terhadap Pengetahuan Santri tentang Pencegahan Konjungtivitis di Pondok Pesantren Raudhatul Ulum Indralaya - Fernandhito, Satria Bagas; Andhini, Dhona; Ningsih, Nurna (PENA NURSING, 2024)
The lack of knowledge among student’s about the prevention of conjunctivitis leads to many students contracting conjunctivitis. Conjunctivitis is the most common eye disease in the world after cataracts and glaucoma. Prevention of conjunctivitis can be achieved by improving personal hygiene, maintaining cleanliness in the invironment, and increasing knowledge about conjunctivitis. One effort that can be made to enhance student’s knowledge about conjunctivitis is by providing health education. This study aimed to determine the effectiveness of health education media on students knowledge about conjunctivitis. This research was a quantitative pre-experimental study with a one-group pretest-posttest design. The sample for this study consisted of 77 students selected throught probability sampling using the cluster sampling technique. The statistical analysis in this study employed the Wilcoxon test. Based on the analysis result, it was found that the short story media significantly influenced students knowledge about the prevention of conjunctivitis ( p-value 0.00(a ≤ 0.05) ). Short story media is highly effective in improving students knowledge about the prevention of conjunctivitis, making it a viable alternative media for health education.